Coronary artery calcification: recent developments in our understanding of its pathologic and clinical significance. (November 2018) - Sakamoto, Atsushi; Virmani, Renu; Finn, Aloke V.
Abstract : Purpose of review: Prior investigations have shown the close association between coronary artery calcification (CAC) and total atherosclerotic plaque burden as well as the risk of cardiovascular and all-cause mortality. However, recent pathologic and imaging-based studies suggested that massive dense calcifications are usually associated with stable plaque; whereas, micro calcifications, especially in the thin fibrous cap, are related to vulnerable characteristics. Further, the molecular mechanisms for initiation/progression of vascular calcification are highly complex and still need to be elucidated. In this manuscript, we discuss recent advancement in our understanding of CAC from the basic, pathologic, and clinical perspectives. Recent findings: Research on the relationship between genetic polymorphisms and CAC has been growing and may potentially lead to future precision-based medicine. In basic research field, more attention has been focused on the relationship between inflammation and vascular calcification. Large-scale imaging based studies support the association between statin and calcification progression, maybe one of the ways by which statins prevent cardiovascular events. Nevertheless, the mechanism responsible for this effect is still not fully understood. Optical coherence tomography has improved resolution to detect CAC over traditional CT and may be especially promising for the detection of calcified nodules. Summary: A better understanding of CAC in all of its forms will advance our understanding of its natural history of atherosclerosis. More work is needed to understand the basic molecular mechanisms responsible for the initiation/progression of CAC, which may eventually lead to the development of effective treatments for atherosclerosis.